2013
DOI: 10.1002/smi.2486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine and Stress on Biomarkers of Cardiovascular Disease in Healthy Men and Women with a Family History of Hypertension

Abstract: The connection between caffeine and its potentially detrimental effects on blood markers of cardiovascular disease (CVD) are controversial. Most studies have focused on cholesterol as a putative mediator of the caffeine-CVD relationship. Other blood markers such as C-reactive protein (CRP) and fibrinogen have been understudied. We examined the effects of caffeine and psychological stress on these CVD markers in healthy, young men and women with a confirmed family history of hypertension. A total of 52 normoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Increased catecholamine and cortisol responses to acute laboratory stressors have been reported in otherwise healthy individuals with parental histories of hypertension (e.g., Bennett et al, 2013;Covelli, 2006;Falkner et al, 1979;Fredrickson et al, 1991;Horikoshi et al, 1985). Our findings show that there are clear differences in circadian catecholamine and cortisol urinary excretion between PH1 and PH2 women as well, suggesting that the parental history difference in the level and variation of these hormones may be more than just an acute reactive phenomenon.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Increased catecholamine and cortisol responses to acute laboratory stressors have been reported in otherwise healthy individuals with parental histories of hypertension (e.g., Bennett et al, 2013;Covelli, 2006;Falkner et al, 1979;Fredrickson et al, 1991;Horikoshi et al, 1985). Our findings show that there are clear differences in circadian catecholamine and cortisol urinary excretion between PH1 and PH2 women as well, suggesting that the parental history difference in the level and variation of these hormones may be more than just an acute reactive phenomenon.…”
Section: Discussionsupporting
confidence: 58%
“…Falkner et al, 1979; Horikoshi et al, 1985; Fredrickson et al, 1991; Covelli, 2006; Bennett et al, 2013). Our findings show that there are clear differences in circadian catecholamine and cortisol urinary excretion between PH+ and PH− women as well, suggesting that the parental history difference in the level and variation of these hormones may be more than just an acute reactive phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cardiovascular responses can attenuate to repeated caffeine exposures such as daily consumption, suggesting that nonsignificant blood pressure and heart rate responses to the caffeine manipulation may be the result of habituation [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…22,23 An experimental study that explored the effects of acute caffeine on BP found no effect on DBP. 24 It is also possible that the adaptation of SBP and DBP to caffeine is different. DBP has been shown to adapt to repeated caffeine exposure, whereas SBP seems to consistently change in response to caffeine.…”
Section: Discussionmentioning
confidence: 99%